74.9k views
0 votes
What is the answer?
5x−(x−11)=21−6x

2 Answers

3 votes

Answer:

1

Explanation:

5x-(x-11)=21-6x

5x-x+11=21-6x

4x+11=21-6x

4x-(-6x)+11=21

4x+6x=21-11

10x=10

x=10/10

x=1

User Layne
by
5.1k points
3 votes

Answer: x=1

Explanation:

Step 1: Simplify both sides of the equation.

5x−(x−11)=21−6x

5x+−1(x−11)=21−6x(Distribute the Negative Sign)

5x+−1x+(−1)(−11)=21−6x

5x+−x+11=21−6x

5x+−x+11=21+−6x

(5x+−x)+(11)=−6x+21(Combine Like Terms)

4x+11=−6x+21

4x+11=−6x+21

Step 2: Add 6x to both sides.

4x+11+6x=−6x+21+6x

10x+11=21

Step 3: Subtract 11 from both sides.

10x+11−11=21−11

10x=10

Step 4: Divide both sides by 10.

10x/10 = 10/10

User Sayou
by
5.0k points